The writing of Richard Falk : towards humane global governance - Falk, Richard (New Delhi, 2012)
Richard Falk has been an inspirational figure for scholars of international law and international relations for more than five decades. His seminal writings, drawing on a range of intellectual traditions, anarchist, humanist, feminist, liberal and Marxist, have offered radical thinking on issues ranging from the Vietnam War and the Israeli-Palestinian conflict to the 9/11 terrorist attacks in the US. A prolific writer, Falk has made path-breaking contributions in clarifying the role of international law in a turbulent world, reforming the United Nations system and promoting international environmental protection and justice. This volume brings together 20 of Falks landmark essays, each resonating with his commitment towards establishing what he calls a system of humane global governance. Divided into five sections, these essays cover a variety of issues: the major challenges before international legal scholarship today, the failure of the United Nations to take the discourse of global democracy and global justice forward, the need to reform the UN, the international communitys focus on protection and sustainability and the neglect of justice and the untapped potential of international human rights law to achieve global justice. The way forward, Falk emphasizes, is to establish, through global social movements, democratic global political structures in the new millennium. The Foreword by B. S. Chimni is a fitting tribute from a well known scholar of international law. He writes, Falk is an embodiment of a critical intellectual who has never hesitated to speak truth to power. Published for the first time in India, The Writings of Richard Falk: Towards Humane Global Governance is a must-read for students and scholars of international law, international relations and political science.
Keywords: International cooperations